Composites of Enteric Polymer/Magnetite: Preparation and Application in Release Processes - Lima, S.V. de; Oliveira, H.P. de (Journal of Applied Solution Chemistry and Modeling, 2012)
The controlled release of drugs represents an interesting procedure applied in the minimization of side effects and in the therapeutic action of pharmacological molecules. With the aim of measuring the kinetics of release of aspirin dispersed in composite of an enteric polymer (Eudragit L-100) in the presence/absence of magnetic particles, we have considered the measurement of fluorescence as a convenient tool. The results indicate that rate of release and amount of dispersed drug in solution varies directly with the concentration of magnetite in the composite, as a consequence of strong interaction between components of microparticles.